Roles of accounting in New Service Development within Servitization – The viewpoint of pragmatic constructivism - Laine, Teemu; Cinquini, Lino; Suomala, Petri; Tenucci, Andrea (Proceedings of Pragmatic Constructivism, 2013)
Motivation & purpose: While acknowledging the importance of servitization, we are concerned about the absence in the academic literature of the roles of accounting in such a transformation (Laine et al. 2012a). We employ pragmatic constructivism (Norreklit et al. 2010) to explore the current and potential roles of accounting in new realities stemming from servitization. Servitization literature in general has not succeeded in providing tools and techniques to support companies under servitization (Baines et al. 2009). Servitization processes typically aim at developing product offerings and customer relationships of the focal companies (Penttinen & Palmer 2007), and thus constitutes a major change at the levels of the servitizing companies, the business units and a number of individuals within. Pragmatic constructivism provides a sound basis for analyzing socially constructed realities, or realities under construction, and is therefore a potential viewpoint for better understanding also servitization processes. More particularly, the employment of facts, possibilities, values and communication as central concepts of pragmatic constructivism could help in outlining the potential roles of accounting in supporting the servitization processes, as it is already been used in the context of accounting supporting strategic level organizational changes (Mitchell et al. 2013). We propose pragmatic constructivism to be used in examining in-depth qualitative data, where it can be a potential viewpoint to provide new knowledge about the new realities of servitization and the roles of accounting enactment from different perspectives. Methodology: The data of the paper comprises a literature review and a survey that constitute the basis for research implications. The review focuses on the identified roles of accounting in servitization within selected thirty-three (33) scholarly journals on service, servitization or accounting. Empirically, the current servitization initiatives as well as the current and potential roles of accounting in servitization are explored within the sample of 451 Finnish and Italian machinery manufacturers. The line of the argument of the paper is the following. First, the knowledge gap of the supportive tools and techniques for servitization is identified and the inquiry is further specified into the roles accounting in supporting servitization. Second, a literature review is conducted to confirm the aforementioned research gap and to preliminary explore the roles of accounting in the new realities resulting from the servitization processes. Third, the survey data is used and reflected upon the review results to better characterize the current servitization initiatives and to examine the current and potential roles of accounting in supporting those initiatives, especially within new offering development. Fourth, pragmatic constructivism is used as a framework to describe the requirements set for accounting by servitization and to outline the unused potential of accounting in supporting servitization. Finally, the paper discusses implications for managing servitization initiatives and proposes an agenda for further research, with an emphasis on in-depth case studies on companies under servitization. Findings: The literature review confirmed the existence of the research gap regarding the roles of accounting in supporting servitization, more particularly regarding New Service Development (NSD) activities. In fact, only a few papers even address explicitly the topic of planning and controlling the servitization. The papers found in the survey emphasized e.g., the importance of understanding values and related business possibilities in the customers’ business (Laine et al. 2012b), identifying the unwanted losses in the existing reality (Shulver 2005) from the viewpoint of the requirements of the new business possibilities, and examining the requirements of measuring the facts and possibilities related to the customer experience (Palmer 2010) so far neglected by many manufacturers. These all set requirements for accounting in servitization. The preliminary survey results reinforce the importance of servitization among machinery manufacturers and also reveal differences in the servitization processes in terms of scope and content and, more importantly, from the viewpoints of different actors, such as general managers, service managers, R&D managers and business controllers. Although many companies systematically manage the offering development for servitization, accounting does not succeed in supporting creativity and succeeds only to some extent in supporting the overall servitization strategy. This might be partly due to the fact that accounting tools available are not widely used in this context. Pragmatic constructivism is thus used in outlining the requirements, current status and future potential for accounting in supporting servitization processes. Besides controlling the servitization initiative, identifying new business facts, possibilities and their value could help different actors in defining and justifying the initiative (Laine et al. 2012a). Moreover, as servitization yields a new (socially constructed) reality for the managers, the information needs (accounting objects) and the roles given for accounting require re-definition. This may be done value creation with (and at) the customers, with renewed costing and pricing tools (see e.g., Barontini et al. 2013). Implications: To enhance the servitization literature, the paper implies an agenda for further research that should include i) defining and positioning the servitization initiatives from multiple actors’ perspectives to outline the requirements set for accounting, ii) examining the current and potential roles of accounting within servitization and iii) focusing particularly on accounting development in this context. More generally, the agenda for further research holds potential in shedding light on the roles of accounting in the strategic change context (Naranjo-Gil & Hartmann 2007, Cinquini & Tenucci 2010, Mitchell et al. 2013), where the realities of the key actors are significantly redefined. Originality/value: The paper responses to a relevant research gap of supporting servitization in different ways with accounting tools and techniques. More particularly, the paper provides a novel perspective to its topic, by approaching the new realities and related accounting implications stemming from servitization, as (potentially) interpreted by the key actors.